STUDY OF READINESS FOR IMPLEMENTATION OF INTEGRATED STUNTING REDUCTION INTERVENTIONS IN KLOJEN DISTRICT, MALANG CITY - Fitria Dhenok Palupi; Indri Hapsari; Ibnu Fajar; Nurul Hakimah; Tapriadi Tapriadi; Juin Hadisuyitno; Siti Rahayu Nadhiroh (Universitas Airlangga, 2022)
be implemented by all policymakers. One of the strategic issues in accelerating stunting reduction in Indonesia is strengthening and increasing institutional capacity in reducing stunting. It is necessary to maintain regulations to ensure the implementation of stunting prevention and control efforts in the regions, and increase knowledge, and community participation. Objective: This study aims to determine the readiness to implement an integrated stunting reduction intervention through the DESA EMAS program at the stunting locus in Klojen District. Research method: This study uses a descriptive study method which was carried out in September – October 2022. The target of the study is regional apparatus organizations at the sub-district level at three stunting in Klojen District. Data collecting in the form of interviews with guided questions related to commitment, supporting factors, inhibiting factors, and sub-district programs. Data analysis was done descriptively in the form of textual. Results: The readiness to implement an integrated stunting reduction intervention through Desa Emas Program can be seen from the commitment of the three loci to stunting handling, cross-sectoral collaboration, and the availability of human resources capable of making three program (DASHAT, Budikdamber and urban farming). Commitment to human resources through the involvement of sub-district officials, sub-district health workers, assistant staff for stunting activities, health development cadres, POSYANDU cadres, and PAUD teachers. Conclusion: The three sub-districts in Klojen District have made efforts to implement stunting management commitments through available resources and limited funding. Keywords: stunting, commitment, Klojen District, Malang City